1998
DOI: 10.1046/j.1365-8711.1998.01974.x
|View full text |Cite
|
Sign up to set email alerts
|

RXTE highlights of the 34.85-day cycle of Her X-1

Abstract: An analysis of the publically available RXTE archive on Her X-1 including data on 23 34.85-day cycles is performed. The turn-on times for these cycles are determined. The number of cycles with a duration of 20.5 orbits has been found exceedingly larger than of shorter (20 orbits) or longer (21 orbits). A correlation between the duration of a cycle and its mean X-ray flux is noted. The mean X-ray light curve shows a very distinct short-on state. The anomalous X-ray absorption dip is found during the first orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…However, our results are insensitive to the choice of uncertainties. Whilst this is a very rough method, the results agree surprisingly well with the more detailed analysis (basically a template fitting method) of Shakura et al (1998). Next a linear ephemeris was fit to the times of the main-ons that occurred before the anomalous lowstate to give a mean 35 day cycle time of 34.8 day, consistent with the model of Staubert et al (1983) where it is proposed that the mean period is 20.5 times the orbital period, i.e., 34.85 day and that the observed on-states can fluctuate around this value by 0 or ± 1 2 orbital cycles.…”
Section: Day Turn-on Timesupporting
confidence: 68%
“…However, our results are insensitive to the choice of uncertainties. Whilst this is a very rough method, the results agree surprisingly well with the more detailed analysis (basically a template fitting method) of Shakura et al (1998). Next a linear ephemeris was fit to the times of the main-ons that occurred before the anomalous lowstate to give a mean 35 day cycle time of 34.8 day, consistent with the model of Staubert et al (1983) where it is proposed that the mean period is 20.5 times the orbital period, i.e., 34.85 day and that the observed on-states can fluctuate around this value by 0 or ± 1 2 orbital cycles.…”
Section: Day Turn-on Timesupporting
confidence: 68%
“…For example, the peaks of each superorbital cycle have a number of prominent dips (see Fig. 4), which appear to be akin to the ''preeclipse dips'' seen in the long-term X-ray light curves of Her X-1 (Shakura et al 1998;Stelzer et al 1999;Klochkov et al 2005). To further reduce the inherent noise in the ASM light curves of SMC X-1, we applied a simple Gaussian smoothing to the unbinned ASM data via a fast Fourier transform (FFT ) 7 with a smoothing scale of 16 data bins ($2.5 days on average).…”
Section: Defining the Superorbital Ephemerismentioning
confidence: 98%
“…Trümper et al (1986) had suggested that the systematic variation in pulse shape is due to free precession of the neutron star: the viewing angle towards the X-ray emitting regions of the neutron star varies with the phase of the neutron star precession. Shakura et al (1998) applied a model of a precessing triaxial shape to pulse profiles of Her X-1 observed by HEAO-1, and Ketsaris et al (2000) did so for profiles observed by RXTE/PCA. Using all observations by RXTE from 1996 until 2005 we have verified that the shape of the pulse profiles is reproduced every ∼35 days.…”
Section: Pulse Profile Variationsmentioning
confidence: 99%